"Traveling-wave tube mechanics simulator suite" a CAD/CAE integrated rapid redesign system of vibration analysis for traveling-wave tubes. (February 2019) - Yin, Jun-Hui; Xu, Li; Xie, Peng; Yang, Zhong-Hai; Li, Bin
Abstract: Traveling-wave tubes (TWTs) are popularly used as the microwave power amplifier in civil and military applications and have a high mechanical sensitivity. It is necessary to understand their vibration characteristics under all operating conditions. To address this issue, a CAD/CAE integrated rapid redesign system of vibration analysis with unified data architecture (UDA) has been developed and presented in this paper. The UDA is presented to make CAD and CAE be an organic entity. This system is composed of the following four layers: (i) CAD/CAE integrated design environment, (ii) parametric modeling and fast modeling platform with custom-built tools, (iii) accurate and fast finite element free vibration analysis solver based on rapid solving techniques of equation, and (iv) fast finite element random vibration analysis solver. The CAD/CAE integrated system concept is typically applied in loop design-analysis-redesign procedures. In this CAD/CAE integrated design system, the designers can freely and rapidly complete component design and performance analysis simultaneously instead of using two different software or two interface environment. To improve the accuracy and efficiency of large-scale finite element vibration analysis, especially for free vibration analysis, an improved Lanczos iteration method with a new three-level preconditioner is developed and pseudo excitation method is introduced to perform random vibration analysis. The new three-level preconditioner is composed of a multifrontal block incomplete cholesky preconditioner, a p -type multigrid preconditioner, and a block Jacobi preconditioner. The developed system has been applied to the design of TWTs and been found to shorten the design cycle significantly compared with ANSYS.